Extensive reading: a meaningful tool to develop critical thinking in ESL students at a university level. - Guevara Jiménez, Laura Haydée; Osorio Rosales, Eldaa Anjanntte Soraya (2024)
Teaching English as an International Language has emerged in response to the global spread of English and the subsequent changing needs of learners. So, ESL students at University level have the necessity of developing many aspects in their studies that can help change their lives. A way to do this is by developing their critical thinking. And a technique of developing this skill is Extensive Reading. Critical thinking can contribute to think about all the possibilities to solve a problem, to consider different points of view and to identify people’s arguments as good contribution or conclusions on a specific topic. The term ESL is used in the work because the literature found that supports the report makes reference to this type of students. This is a tool mostly used and applied in other countries, and there is evidence of it. This happens because even though when students get to a university level even they have taken different subjects in which they are required to read. It is difficult for them to do that since they have not been developed that habit in those previous school years of study. Also this topic was focused on ESL students rather than EFL students because there are many references available and there exist communities which are using these tools. While with EFL no reference is available at the university and in the country. The ESL term, as a primary setting to show the university that other countries use these tools, which benefit students, to obtain better academic, professional and personal development. So this paper is intended to motivate students and teachers to start investigating and applying Extensive Reading and Critical Thinking in their lives; it is intended for them to present some advantages these two skills can provide so that they can continue developing this habit for the rest of their lives. Reading is a tool to obtain information around the world. This ability provides thoughts that encourage students to think; and when people think they can shape their lives and they can choose how to live, act and make decisions. Students canals learn through this skill how to question and analyze the information supplied in various forms. These were the main reasons of choosing this topic because they help us analyze how extensive reading helps develop the critical thinking skill in ESL students at a University level. This research work is divided in several parts. The first one is the introduction which gives a general view of the development of this research paper. The second part is the objectives. These objectives set the goals to reach while this research is carried out. The third part includes the justification which states the reasons why this research is important and the ones who will be benefited by. The fourth part is the body of the research paper. Here the importance of extensive reading as a meaningful tool to develop critical thinking skills is developed. The fifth part is the conclusion of the research work. It summarizes the principal points of the research paper. Then the sixth part describes the recommendations to take into account for possible changes in the study of English. The seventh part is related to the methodology which explains briefly the steps followed to carry out the work. As the last part of this research paper there is the bibliography, which lists all the books, websites and articles consulted to support the arguments established for extensive reading and critical thinking.